Strategi Bersaing Agroindustri Susu Kedelai Bubuk (Studi kasus: industri sgn di kota pekanbaru) - Yudi Saputra; Syaiful Hadi; Arifudin ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This studyaims to analyze the internal and external environment and accomplish the competitive strategy for agro-industry entrepreneurs of SGN soybean milk powder. A'WOT analysis which combines AHP and SWOT was used Expert Choice 2000 Software. The results of this research thatindicated the priority strategy for the agro-industry development of SGN soybean milk powder are (1) Product development (2) Optimizing available resources, (3) Efficiency with reducing production cost, (4) Improving the quality of human resources through training regularly, (5) Maintaining the quality and image of the product, (6) Utilizing the KUR program from the Government and (7) Coordinate with relevant parties to inhibit the entry of newcomers. Keywords: competitive strategy, SGN soybean milk powder, strategic priorities